A rare case of blunt trauma abdomen leading to isolated grade 4 pancreatic injury - Swami, Ganesh A.; Punpale, Ajay; Halnikar, Chandrashekhar S.; Samudre, Sayali S. (International Surgery Journal, 2021)
Isolated pancreatic injury due to blunt trauma abdomen is a rare case in children and is associated with higher morbidity and mortality rates. We present a case of isolated grade 4 pancreatic injury in a 12 years old male child, presented with history of trauma to abdomen by bicycle handle, pain in abdomen, abdominal distention and vomiting. Ultrasonography of revealed hemoperitoneum with peri-pancreatic fluid collection, Contrast enhanced Computed tomography of abdomen and pelvis showed grade 4 pancreatic injury with mild hemoperitoneum. Emergency exploratory laparotomy was done and saponified part of pancreas along with omentum was debrided and Roux-en-Y pancreaticojejunostomy was performed. Procedure was uneventful and patient recovered well in post-operative period. In conclusion, isolated grade 4 pancreatic injury is a rare presentation following blunt trauma to abdomen and conservative approach as well as many operative procedures have been described for treatment of such injury. Roux-en-Y pancreaticojejunostomy procedure can be considered as a definitive treatment in such cases and to avoid long term complications.